Improvement in the intrinsic water use efficiency of sugarcane by intergeneric hybridization with Erianthus arundinaceus - Takaragawa, Hiroo; Terajima, Yoshifumi; Okamoto, Ken (Frontiers in Plant Science, 2025)
IntroductionSugarcane (Saccharum spp.) is often grown under unstable rainfall and drought conditions, highlighting the need for improved drought tolerance. Erianthus arundinaceus, a closely related species, shows high intrinsic water use efficiency (iWUE) and robust root formation capacity. However, research on improving sugarcane leaf traits using Erianthus is limited. This study aimed to evaluate the water use efficiency and associated leaf traits of sugarcane × Erianthus intergeneric F1 hybrids and their parental genotypes under both wet and dry pot conditions in a greenhouse to assess the potential for improving drought tolerance through intergeneric hybridization.MethodsThe sugarcane cultivars (drought-susceptible NiF8 and drought-tolerant Ni9), Erianthus accessions (JIRCAS1 and JW630), and their intergeneric F1 hybrids (NiF8 × JIRCAS1 and NiF8 × JW630) were evaluated for gas exchange and leaf morphology.ResultsErianthus accessions had superior stomatal responses, lower stomatal conductance, and higher iWUE than NiF8, with JW630 showing higher iWUE than Ni9. However, Erianthus accessions had lower gravimetric water use efficiencies (gWUE) than the sugarcane cultivars, likely due to the higher leaf area ratio (LAR). The hybrids displayed higher iWUE, with dry matter partitioning characteristics resembling those of sugarcane (low LAR, high shoot/root ratio, and high partitioning to the stem), suggesting potential for higher gWUE under field canopy conditions. The high iWUEs of Erianthus and F1 hybrids were suggested to be attributed to the fewer stomata on the abaxial surface.ConclusionThis study highlights Erianthus’s potential in improving leaf characteristics to enhance sugarcane drought tolerance because the hybrids demonstrated “best of both worlds” scenario, where they inherited high iWUE from Erianthus with favorable biomass partitioning characteristics from sugarcane.